Weight Control Related Eating Habits and Nutritional Knowledge of Male and Female College Students - Lee, Joo-Eun (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: In this study, 400 college students in Cheongju were surveyed for weight control related eating habits and nutritional knowledge to provide basic data for healthy eating in adulthood.Methods/Statistical analysis: Frequency analysis was performed on general information of college students, and BMI, weight control experience, and residence were analyzed by χ2-test for distribution of men and women, and for weight control satisfaction, taste preference, eating habits, and nutritional knowledge, the mean and standard deviation were calculated and then an independent-samples t-test was conducted for both sexesFindings: The results showed that the BMI distribution of the college students was normal 54.3%, underweight 20.3%, overweight 12.0% and obese 13.4%, among which weight control experience was 68.7%. There was a significant difference in the distribution of male students in the BMI distribution as the proportion of obese was higher than female students (p